Bone mineral density in the leopard tortoise: Implications for inter-taxon variation and bone survivorship in an archaeozoological assemblage. (30th November 2018) - Holt, Sharon; Codron, Daryl; Horwitz, Liora Kolska
Abstract: In this study we present data on bone mineral density (BMD) values for the cranial and post-cranial skeleton of the leopard tortoise ( Stigmochelys pardalis ). We found significant inter and intra-skeletal variation in different values of BMD within this species. The intra-skeletal, but not inter-skeletal pattern, was comparable to that of terrestrial mammals of similar size, despite differences in bone structure. Overall, the tortoise has bone density that is intermediate between that of leporids (rabbits/hares) on the one hand and canids (dogs/wolves etc.) and marmots on the other. In this study we have used random effects to test regression models of BMD and demonstrate their value over the simple linear regression models that are currently in use. Finally, we applied the modern leopard tortoise proxy data to test whether different parameters of BMD impact survivorship of tortoise bones in the Holocene strata from Wonderwerk Cave (Northern Cape Province, South Africa). Results indicate that this assemblage has undergone some degree of bone density-mediated attrition, probably influenced by burning and deposition time rather than animal agents.